Cytogenetic toxicity from pesticide and trace element mixtures in soils used for conventional and organic crops of Allium cepa L. (1st May 2021) - Gallego, Jorge L.; Olivero-Verbel, Jesus
Abstract: Pesticides and trace elements occur in complex mixtures in agroecosystems, affecting soil health and food security. Hence, it is necessary to determine their toxicity in field conditions and to develop monitoring approaches to assess conventional and organic agriculture. The aim of this research was to evaluate the associations between Allium cepa L. cytogenetic biomarkers and the realistic mixture of pesticides and trace elements found in soils of conventional, conversion, and organic crops in an intensive agricultural region in Colombia. Pesticide screening was conducted using GC-MS/MS and LC-MS/MS methods. Arsenic, cadmium, lead, and zinc were analyzed by ICP-MS; chromium, copper, nickel, and selenium by ICP-OES; and mercury by a direct analyzer. The meristematic cells in roots of Allium cepa L. were analyzed through microscopic observations to quantify cytogenetic effects. In conventional crops, 26 pesticides were detected in the soil samples, and those were below the limit of quantification in organic crops. The mean levels of As, Cd, Cr, Ni, Pb, and Se were also greater in soils of conventional crops compared to the organics. In addition, the biomarkers of cytotoxicity and genotoxicity appeared augmented in conventional samples, and those were correlated with pesticide and trace element concentrations, pollution indices, and hazard quotients. Subsequently, a discriminant function based on the mitotic index, chromosomal aberrations, and nuclear abnormalities was suitable to classify the samples by crop type. These results demonstrate the sensitivity of Allium cepa L. to the toxicity of complex mixtures in field crops and its potential as an in-situ approach for soil health monitoring in organic and conventional crop systems. Graphical abstract: Image 1 Highlights: Fungicides, herbicides, and insecticides were detected in soils of onion crops. Allium cepa L. biomarkers were assessed under field realistic conditions. Pesticides and metals in agricultural soils pose genotoxic effects on Allium cepa L. Crop types were classified by discriminant analysis of Allium cepa L. biomarkers. Allium cepa L. was sensitive in-situ to the toxicity of complex mixtures in soils.